COMPÓSITO NANOESTRUTURADO DE ALUMINA-ZIRCÔNIA PARA PRÓTESE ODONTOLÓGICA - Ojaimi, Christiane Lago (2014)
The search for a beautiful and harmonious smile has motivated research on ceramic materials for dentistry aiming at the elimination of the metal substructure. Among many dental devices, abutments for implants are one component that has been replaced by ceramic material. The ceramics that exhibit good biocompatibility and mechanical properties are alumina and zirconia, the latter being the material the most widely used ceramic abutments. Both alumina and zirconia as present some restrictions when used only, but the ceramic base of alumina and zirconia compounds can present improved property compared with the isolated materials. Studies exhibit that alumina-zirconia nanocomposites present agreat improvement in some mechanical properties. Since the national production of ceramic abutments is still low compared to international production, and ceramic abutment with alumina and zirconia is not widespread. This work aims studying the sintering in two and three steps process of ceramic alumina nanocomposites with nanometric inclusion of 15% by volume of zirconia, aiming the application as dental abutment. For this purpose, samples were produced by pressing and sintered using different sintering conditions. The characterization of the sintered nanocomposites was made by X-ray diffraction, scanning electron microscopy and measurements of grain size, and mechanical properties were evaluated from Vickers microhardness and fracture toughness. To evaluate the hydrothermal stability of these nanocomposites, accelerated aging tests were done in an autoclave and the samples were characterized by atomic force microscopy and X-ray diffraction. The results showed that sintering in steps allowed in the refinement of the microstructure of nanocomposites and that were resistant to hydrothermal degradation.